Genesis and Morphotectonic Characterisation of Crescent- Shaped feature from Alcock Rise, Andaman Sea - Sachin Kumar Tripathi; Resmi Sathikumar; Jishnu Balagangadharan Kaustubhakumari; Priyanka Dey Guha; Soibam Ishwarchandra Meitei (BULLETIN OF THE MARINE GEOLOGY, 2019)
Study of 98 crescent shape depressions over Alcock Rise, Andaman Sea were reported for the first time in between water depth -500 and -2000 m using multibeam swath bathymetry data. These gigantic depressions have crescent length (CL) varies from 600 to 3800 m and width (CW) varies from 200 to 2500 m with an average central depression of 500 m. Detailed parametric characterization reveals that slope and axial ratio of these crescentic structures have no direct relationship with general shape and steepness of their escarpment. Moreover, spatial distribution of these structures show a clustering of elongated crescent with higher crescent length to width ratio in NW margin of Alcock Rise compare to centre. This change in shape from open elliptical to semicircular depression probably suggests that earlier formed open crescents were modified at later stage to semicircular depressions. As observed in the seismic data, the formation of the crescentic depressions were initiated by the normal fault in-association with major dextral transform fault and subsequently its geometry was modified by local transpression along with seismicity induced slumping and bottom current scouring from the weaker zones. So, tectonics and bottom current activity provides simpler explanation for the formation of crescentic structure over Alcock Rise.Keywords: Crescentic depression, Alcock Rise, Swath bathymetry, Bottom current, Normal fault.